Casing Casemethod Methods - Dooley, Arch R.; Skinner, Wickham (Academy of Management Review, 1977)
In this article the authors acknowledge the wide variety of case method approaches to conducting research as well as the numerous ways the technique is used as a teaching tool. They attempt to open up a dialogue between academics and discuss the various uses of the case method in order to establish a wider variety of educational techniques in management education. They authors relate their experience of sitting in on several classes where the teacher made use of the case method and discuss the differences and similarities they noticed. They discuss several of the different instructor styles they viewed such as the facilitator instructor, the coach instructor, the quarterback instructor and the demonstrator instructor.